Derivados modificados de tiossemicarbazonas e diclofenaco: perfil farmacológico e efeito da coordenação a metais - Jeferson Gomes da Silva (2013)
The present work involved the syntheses and an investigation of the pharmacological profile of chalcone-derived thiosemicarbazones, a hydrazone from diclofenac and their metal complexes aiming the preparation of new antimicrobial, antitumor and anti-nociceptive agents. 3-phenyl-1-(2-pyridil)-prop-2-en-1-one thiosemicarbazone [HPyCTPh (1)], 3-(4-chlorophenyl)-1-(2-pyridil)-prop-2-en-1-one thiosemicarbazone [HPyCT4ClPh (2)], 3-(4-bromophenyl)-1-(2-pyridil)-prop-2-en-1-one thiosemicarbazone [HPyCT4BrPh (3)] and 3-(4-nitrophenyl)-1-(2-pyridil)-prop-2-en-1-one thiosemicarbazone [HPyCT4NO2Ph (4)] were obtained from 3-phenyl-1-(2-pyridil)-prop-2-en-1-one (PyCPh), 3-(4-chloro-phenyl)-1-(2-pyridil)-prop-2- en-1-one (PyC4ClPh), 3-(4-bromo-phenyl)-1-(2-pyridil)-prop-2-en-1-one (PyC4BrPh) and 3-(4- nitro-phenyl)-1-(2-pyridil)-prop-2-en-1-one (PyC4NO2Ph). The Ga(III) (Ga1-Ga4) and Fe(III) (Fe1-Fe4) complexes with 1-4 are of the [M(L)2]NO3 type and the Zn(II) complexes (Zn1-Zn4) of the [Zn(L)2] type, HL = thiosemicarbazone. In these cases the thiosemicarbazones attach to the metal center through the Npy-N-S chelating system. The Cu(II) complexes (Cu1-Cu4) are of the [Cu(HL)Cl2] type, where HL stands for the zwitterionic thiosemicarbazone which binds to the metal through the N-S chelating system. The chalcones proved to be active against Staphyloccocus aureus bacteria and Candida albicans fungi but were inactive against Pseudomonas aeruginosa. In many cases the thiosemicarbazones revealed to be more active than the chalcones. The complexation of the thiosemicarbazones to Ga(III) and Cu(II) resulted in more active compounds. The cytotoxic effect of the chalcones, thiosemicarbazones and the Ga(III) e Cu(II) complexes was studied against HCT-116 (colorectal carcinoma) and MCF-7 or MDA-MB 231 (mammary carcinomas) solid tumor cell lines, and against HL-60 (myeloid leukemia) and Jurkat (limphoyd leukemia). The chalcones proved to be the less active compounds. In general the thiosemicarbazones were more cytotoxic than the chalcone precursors. 1, Ga1, 2, Ga2, 3 and Ga3 revealed to be more active than cisplatin against HCT-116 cells. The thiosemicarbazones and the Ga(III) complexes exhibited similar capacity as cisplatin to inhibit the growth of HL-60 cells. Except for 1, the IC50 of all compounds was lower than that of cisplatin against HL-60 cells. The IC50 of the Ga(III) complexes were lower than those of the free thiosemicarbazones against this cell lineage, indicating that coordination to Ga(III) was a good strategy for cytotoxicity improvement. In general, the thiosemicarbazones and their Cu(II) complexes were able to inhibit at least 75% of proliferation of leukemia, MDA-MB 231 and HCT-116 cells at 10 µM. Upon coordination to Cu(II) cytotoxicity improved. Many of the studied compounds were active with IC50 values in the nanomolar range. The thiosemicarbazones and Cu4 were able to induce DNA fragmentation in HL-60 cells, indicating their pro-apoptotic potential. Similarly all Cu(II) complexes induced the appearance of 75% of subdiploid DNA content in MDA-MB 231 and HCT-116 cells. However a low level of subdiploid DNA content was observed in the presence of the free thiosemicarbazones, suggesting that their mechanism of action might be different from those of the complexes. Cu1-Cu3 were able to interact with bovine serum albumin and with DNA by an intercalative process. We prepared pyridoxal diclofenac hydrazone hydrochloride (H3PDHCl, 5) and its [Cu(H2PDH)Cl]Cl∙2H2O (Cu5) and [Ga(HPDH)2]NO3∙4H2O (Ga5) complexes. 5 showed activity in the nociceptive response induced by zymosan A at a molar dose fourfold higher than that of sodium diclofenac. However, unlike diclofenac, 5 did not cause the appearance of gastric lesions, suggesting that it could be an anti-inflammatory drug candidate. 5 did not show antimicrobial or cytotoxic properties and was able to chelate Zn(II) and Cu(II). Hence it could be interesting as anti-Alzheimer drug candidate.